Klaten Laris Square - Nurhasan, Tymar; , Dr. Ir. Arya Ronald; , Ir. Alpha Febela P, MT (2016)
Klaten Laris is a container Square shopping and leisure activities as activities supporting the planned first in Klaten, which will become a superior shopping and an icon. The location at Jalan Pemuda or Center of Klaten City. This facility is intended to the public low end to high end. Square concept aims to facilitate activities required. Atrium and garden as indoor and outdoor activity space. Is equipped to support the shopping activity to make it more enjoyable. Klaten Laris Square offers functions in the building. Subsistence, enjoyment as a place for recreation and fitness as a container of light exercise into a single unit. Appearance of the building follows the function of the building or form follow function.